Sanitary protection of the territory of Russian Federation. Report 3. Threelevel control system of epidemiological risks for infectious diseases, dangerous for humans, at municipal level - V. A. Vishnyakov; A. K. Noskov (Acta Biomedica Scientifica)
Emergency situations associated with infectious diseases dangerous for humans are actual for the Russian Federation. The probability of the occurrence of these events varies for different Russian Federation regions, but also for the individual municipalities of one region. Complex approach to the organization of anti-epidemic readiness for such situations is necessary. This approach should be based on differentiation of municipalities of a Russian Federation region according to the estimation of external and internal epidemiological risks associated. with diseases dangerous for humans. At the federal level the system of epidemiological surveillance is determined for diseases requiring measures for sanitary protection of the territory, and separately for almost every infectious disease, affecting the sanitary-epidemiological welfare of the population of the Russian Federation. In the frames of this study it is offered to consider the probability of the importation of infectious diseases, requiring measures for sanitary protection of the territory, as the external epidemiological risk. Diseases common to man and. animals, other endemic to the Russia infectious diseases, including relevant in regional pathology, are viewed as the potential and real internal epidemiological risk. The purpose of this study is the development of the control system of these epidemiological risks at the Municipal level. The three-level control system of the epidemiological risks according to differentiation of municipalities of a Russian Federation region by criteria of external and. internal epidemiological risks is proposed as a result of this work. The control system allows suggesting a priority orientation of organizational, preventive and anti-epidemic actions in municipalities and. promotes rational distribution of forces and means of Public Health Institutions in cases of emergency situations in the field of sanitary-epidemiological welfare associated with diseases dangerous for humans.